Traduire Reclus. L’Italie écrite par Attilio Brunialti - Federico Ferretti (Unité Mixte de Recherche 8504 Géographie-cités, 2009)
The Italian edition of the Nouvelle Géographie Universelle isn’t completely faithful to original text, because its translator and editor Attilio Brunialti, geographer, jurist, politician belonging to Depretis’ party, and very engaged for Italian colonialism, adds two volumes about Italy completely written by him, although all the work remains signed by the name Eliseo Reclus. Crossing the two texts about Italy, we discover two perspectives, similar in some aspects, but very different in many others, about geography, society and politics of the young Italian nation during the Age of the Empires.